Healthy reviews! Online physician ratings reduce healthcare interruptions - Michael E. Kummer; Ulrich Laitenberger; Cyrus E. Rich; Danny R. Hughes; Turgay Ayer (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
We show that review platforms reduce healthcare interruptions for patients looking for a new physician. We employ a difference-in-differences strategy using physician retirements as a 'disruptive shock' that forces patients to find a new physician. We combine insurance claims data with web-scraped physician reviews and highlight a substantial care-gap resulting from a physician's retirement. We then show that online physician reviews reduce this gap and help patients find a new physician faster. Our results are robust to including a variety of controls and various instruments for the availability of physician reviews, but are not found for patients of nonretiring physicians. By reducing interruptions in care, reviews can improve clinical outcomes and lower costs.
Keywords: I1; I11; I2; O33; 330; Healthcare; Online physician ratings; Online physician reviews; Care-gap